Combination Therapy with Disulfiram, Copper, and Doxorubicin for Osteosarcoma: In Vitro Support for a Novel Drug Repurposing Strategy. (11th July 2019) - Mandell, Jonathan B.; Lu, Feiqi; Fisch, Matthew; Beumer, Jan H.; Guo, Jianxia; Watters, Rebecca J.; Weiss, Kurt R.
Abstract : Although many cancer cells have significantly higher copper concentrations compared with normal cells and tissues, the role of copper in cancer biology and metastatic disease remains poorly understood. Here, we study the importance of copper in osteosarcoma, which frequently metastasizes to the lungs and is often chemoresistant. K12 and K7M2 are murine OS cells with differing metastatic phenotypes: K7M2 is highly metastatic, whereas K12 is much less so. Intracellular copper levels were determined using atomic absorption. Copper transporters were quantified by qPCR. Cytotoxicity of doxorubicin, disulfiram, and copper(II) chloride was assessed with a cell viability fluorescence stain. Additionally, K7M2 viable cell counts were determined by trypan blue exclusion staining after 72 hours of treatment. Copper levels were found to be significantly higher in K12 OS cells than in K7M2 cells. qPCR showed that K12 cells upregulate the copper influx pump CTR1 and downregulate the copper efflux pump ATP7A compared to K7M2 OS cells. Combination treatment of copper chloride (50 nM) with disulfiram (80 nM) was only cytotoxic to K12 cells. Triple treatment with doxorubicin, disulfiram, and copper displayed potent and durable cytotoxicity of highly metastatic K7M2 cells. We demonstrate here that murine OS cell lines differing in metastatic potential also vary in endogenous copper levels and regulation. Additionally, these differences in copper regulation may contribute to selective cytotoxicity of K12 cells by extremely low doses of copper-potentiated disulfiram. The combination of doxorubicin, disulfiram, and copper should be explored as a therapeutic strategy against OS metastases.